The Influence of Legal Literacy and Law Enforcement Effectiveness on Cybercrime Prevention - Sumarna Sumarna (UNISSULA, 2025)
This study examines the influence of legal literacy and law enforcement effectiveness on the prevention of cybercrime. As cybercrimes increasingly pose threats to individuals, organizations, and governments worldwide, understanding how legal awareness and the effectiveness of law enforcement mechanisms contribute to mitigating these crimes is crucial. The study uses a quantitative research design, with data collected from 300 respondents, including internet users and 50 law enforcement officers in Indonesia. The results indicate that higher legal literacy significantly correlates with better cybercrime prevention, as individuals with greater legal awareness are more proactive in protecting themselves online. Furthermore, the study finds that effective law enforcement, characterized by timely responses and adequate training for officers, plays a vital role in reducing cybercrime. The regression analysis confirms that both legal literacy and law enforcement effectiveness positively influence cybercrime prevention. Based on these findings, the study recommends enhancing legal education and improving law enforcement training to create a more secure digital environment. The study provides valuable insights for policymakers and law enforcement agencies to develop comprehensive strategies for cybercrime prevention, emphasizing the need for improved public legal awareness and stronger institutional capabilities.